2015
DOI: 10.1016/j.febslet.2015.08.026
|View full text |Cite
|
Sign up to set email alerts
|

Three cellulosomal xylanase genes inClostridium thermocellum are regulated by both vegetative SigA (σA) and alternative SigI6 (σI6) factors

Abstract: a b s t r a c tClostridium thermocellum efficiently degrades crystalline cellulose by a high molecular weight protein complex, the cellulosome. The bacterium regulates its cellulosomal genes using a unique extracellular biomass-sensing mechanism that involves alternative sigma factors and extracellular carbohydrate-binding modules attached to intracellular anti-sigma domains. In this study, we identified three cellulosomal xylanase genes that are regulated by the r I6 /RsgI6 system by utilizing sigI6 and rsgI6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 62 publications
1
14
0
Order By: Relevance
“…Interestingly, the C. thermocellum genome encodes eight alternative RNAP sigma I factors ( I1 to I8 ), of which six, I1 to I6 , were shown to be involved in regulating cellulosomal components (8)(9)(10)(11). The cognate membrane-associated anti-I factors (RsgI1 to RsgI6) contain C-terminal CBMs that are displayed on the cell surface, suggesting that they serve as putative sensors for extracellular polysaccharide substrates (8)(9)(10)(11). Recently, using a heterologous B. subtilis host system, we showed that the C. thermocellum alternative RNAP factors I3 and I6 recognized a predicted I -dependent promoter of the primary scaffoldin gene cipA, located approximately 850 bp from the start codon (10).…”
mentioning
confidence: 99%
“…Interestingly, the C. thermocellum genome encodes eight alternative RNAP sigma I factors ( I1 to I8 ), of which six, I1 to I6 , were shown to be involved in regulating cellulosomal components (8)(9)(10)(11). The cognate membrane-associated anti-I factors (RsgI1 to RsgI6) contain C-terminal CBMs that are displayed on the cell surface, suggesting that they serve as putative sensors for extracellular polysaccharide substrates (8)(9)(10)(11). Recently, using a heterologous B. subtilis host system, we showed that the C. thermocellum alternative RNAP factors I3 and I6 recognized a predicted I -dependent promoter of the primary scaffoldin gene cipA, located approximately 850 bp from the start codon (10).…”
mentioning
confidence: 99%
“…, Table S1), indicating that the glucose‐derived cellulosome was steadily produced at low level, while the cellulosome synthesis with cellobiose and Avicel was greatly stimulated compared to glucose. According to previous reports, the expression of cellulosomal genes is regulated by both the primary sigma factor SigA and the alternative sigma factor SigI (Nataf et al ., ; Sand et al ., ; Munoz‐Gutierrez et al ., ). The housekeeping SigA is for constitutive cellulosome synthesis at low level, while the environment‐sensitive SigIs induce the high‐level production of the cellulosome.…”
Section: Resultsmentioning
confidence: 98%
“…Until now, the knowledge we have regarding the regulation of cellulosomal genes by C . thermocellum σ I -like factors is a recent report of Sand and co-workers [ 27 ] which showed that the xylanase genes xyn10Z (or Clo1313_2635 according to the DSM 1313 genome annotation), xyn11B (Clo1313_0522) and xyn10D (Clo1313_0177) were under the control of σ I6 . Previously, Nataf and co-workers [ 19 ] showed that the cellulase gene celS ( cel48S ) was likely under the control of σ I1 .…”
Section: Introductionmentioning
confidence: 99%